2018
DOI: 10.1037/abn0000324
|View full text |Cite
|
Sign up to set email alerts
|

Are there sex differences in the etiology of youth antisocial behavior?

Abstract: Sex differences in the etiology of youth antisocial behavior are an intuitively appealing hypothesis given the consistently higher prevalence of antisocial behavior in boys versus girls. Although a few early studies supported this possibility, reporting stronger genetic influences in females and stronger environmental influences in males, subsequent meta-analyses found that antisocial behavior was equally heritable in males and females. Critically however, none of the meta-analyses evaluated whether sex differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 76 publications
3
21
0
Order By: Relevance
“…Next, given the power hungry nature of these models, we also regressed sex out of the child CP data prior to analysis. Fortunately, this decision is in keeping with prior meta-analyses arguing against sex differences in heritability estimates for child CP (Burt, 2009 a ), as well as recent work indicating the absence of joint etiologic moderation of CP by sex and neighborhood disadvantage (Burt et al ., 2018). Next, our CP data were log-transformed prior to analysis to adjust for positive skew, which can either artefactually inflate or suppress evidence of GxE.…”
Section: Discussionmentioning
confidence: 99%
“…Next, given the power hungry nature of these models, we also regressed sex out of the child CP data prior to analysis. Fortunately, this decision is in keeping with prior meta-analyses arguing against sex differences in heritability estimates for child CP (Burt, 2009 a ), as well as recent work indicating the absence of joint etiologic moderation of CP by sex and neighborhood disadvantage (Burt et al ., 2018). Next, our CP data were log-transformed prior to analysis to adjust for positive skew, which can either artefactually inflate or suppress evidence of GxE.…”
Section: Discussionmentioning
confidence: 99%
“…The TBED-C includes a population-based arm, recruited via birth records ( N = 528 families; monozygotic n = 260, dizygotic n = 268), and an at-risk arm, also recruited via birth records but additionally identified as living in neighborhoods with higher-than-average levels of poverty ( N = 502 at-risk families; monozygotic n = 166, dizygotic n = 336). Detailed information regarding the design, recruitment procedures, and participation rate of the TBED-C is available elsewhere (Burt, Klump, Gorman-Smith, & Neiderhiser, 2016; Burt, Slawinski, & Klump, 2018). All procedures were approved by the institutional review board of Michigan State University.…”
Section: Methodsmentioning
confidence: 99%
“…Page 15 and/or E differ, such that they are more important in one sex versus the other Although the genes and environments influencing ASB do not vary across sex, they account for more variance (i.e., matter more) in one sex versus the other. In scholastic contexts, for example, ASB is more genetic in origin in girls than in boys (Burt et al, 2018).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…When the original meta-analytic data analyzed in Burt (2009a) were additionally disambiguated by informant (Burt et al, 2018), however, the conclusion changed: rather than no quantitative sex differences in etiology at all, the data indicated that there were no sex differences in etiology when ASB was assessed using maternal informant-reports of child behavior. When examining teacher informant-reports of child ASB, however, ASB was more shared environmental in origin in boys than in girls, but more genetic in origin in girls than in boys -a conclusion that persisted to an independent twin sample not included in the original meta-analysis (Burt et al, 2018). Such findings are thought to reflect the 'attribution bias context model', whereby mothers and teachers are exposed to different slices of the child's behavior and thus develop different opinions/attributions regarding the same child (De Los Reyes and Kazdin, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation